Treatment Outcome Comparison Between Telepsychiatry and Face-to-face Buprenorphine Medication-assisted Treatment for Opioid Use Disorder: A 2-Year Retrospective Data Analysis. Issue 2 (March 2017) - Zheng, Wanhong; Nickasch, Michael; Lander, Laura; Wen, Sijin; Xiao, Minchan; Marshalek, Patrick; Dix, Ebony; Sullivan, Carl
Abstract : Objectives: To retrospectively review clinic records to assess the difference between face-to-face and telepsychiatry buprenorphine medication-assisted treatment (MAT) programs for the treatment of opioid use disorder on 3 outcomes: additional substance use, average time to achieve 30 and 90 consecutive days of abstinence, and treatment retention rates at 90 and 365 days. Methods: Medical records of patients (N = 100) who were participating in telepsychiatry and in face-to-face group-based outpatient buprenorphine MAT programs were reviewed and assessed using descriptive statistical analysis. Results: In comparison with the telepsychiatry MAT group, the face-to-face MAT group showed no significant difference in terms of additional substance use, time to 30 days ( P  = 0.09) and 90 days of abstinence ( P  = 0.22), or retention rates at 90 and 365 days ( P  = 0.99). Conclusions: We did not find any significant statistical difference between telepsychiatry buprenorphine MAT intervention through videoconference and face-to-face MAT treatment in our Comprehensive Opioid Addiction Treatment model for individuals diagnosed with opioid use disorder in terms of additional substance use, average time to 30 and 90 days of abstinence, and treatment retention rates.